Unveiling Resilience in Mathematics Education: Exploring the Impact of Age and Gender in Sanggar Bimbingan Rawang, Selangor, Malaysia - Nusaibah, Klarisa Afif; Ekayanti, Arta; Jumadi, Jumadi; Murniati, Murniati (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research focuses on analyzing the impact of gender and age on students’ mathematical resilience. The purpose of this study is to contribute to readers’ understanding of the variability of mathematical resilience among Sanggar Bimbingan Rawang students by considering gender and age roles. Specifically, this study aims to: (1) determine the effect of gender on mathematical resilience, (2) determine the effect of age on mathematical resilience, and (3) determine the effect of the interaction between gender and age on students’ mathematical resilience. This research uses a quantitative approach, conducted on 26 samples from Sanggar Bimbingan Rawang, Selangor, Malaysia. Data collection was performed using questionnaires. The analysis technique involved a prerequisite test, including a normality test and a homogeneity test, followed by a hypothesis test using two-way variance analysis with unequal cells. Based on the data analysis results, it was found that: (1) the significance value indicates no gender influence on mathematical resilience, (2) the significance value of the age variable shows no effect of age on mathematical resilience, and (3) the significance value of the combined gender and age variables shows no interaction between gender and age on students’ mathematical resilience. In conclusion, the findings suggest that neither gender nor age, nor their interaction, have a significant impact on the mathematical resilience of students at Sanggar Bimbingan Rawang. This indicates that other factors may play a more crucial role in influencing mathematical resilience among these students.